Common understanding on international standards and gateways for central securities depository and real time gross settlement (csd-rtgs) linkages. ([Manila] Asian Development Bank, 2019)
Prepared for the Cross-Border Settlement Infrastructure Forum (CSIF) to support its efforts to establish central securities depository and real-time gross settlement linkages. Aims to build a common understanding among CSIF members about international standards and gateways for these linkages.
Keywords: Finance; Asia; Electronic books